Measure of urban-rural transformation in Beijing-Tianjin-Hebei region in the new millennium: Population-land-industry perspective - Yang, Yuanyuan; Liu, Yansui; Li, Yurui; Li, Jintao (Land use policy, 2018)
•An indicator system was established to measure urban-rural transformation from the perspective of population-land-industry.•Urban-rural transformation development was divided into four categories.•Spatio-temporal variations and internal mechanisms of BTH’s urban-rural coordinated transformation were captured. Since the turn of the new millennium, urban-rural transformation has entered a critical period. Ever-widening gaps between urban and rural areas are common in most parts of China. The Beijing-Tianjin-Hebei (BTH) region, as the capital circle of China, has experienced significant urban-rural transformation with accelerated urbanization. On the basis of space analytic geometry, this study measures BTH’s urban-rural transformation by establishing an indicator system from the population-land-industry perspective to capture spatio-temporal variations and explore the internal mechanisms of BTH's urban-rural transformation. The results indicate that the urban-rural system in the BTH region has undergone an intensive and dramatic transformation during 2000–2015. Evolving from basic to advanced and from disorder to order, urban districts in Beijing and Tianjin have always had levels of coordinated transformation degrees (CTD) higher than those of the surrounding high-level counties while the overall coordinated deviation degree (CDD) has exhibited a decreasing trend over time. Four functional zones, which are dominant transition area, key transition area, potential transition area and restricted transition area, of urban-rural transformation were established by adopting the trajectory computing method. This research could track the development process of regional urban-rural change from the essence of an urban-rural system itself. When this indicator system that measures urban-rural transformation is applied in other countries, national differences such as differences in urban-rural structures, as well as the limitations, should be noted.